Pengembangan Agro Techno Park (ATP) di Desa Donowarih Berbasis Diversifikasi Olahan Jeruk - Sri Suhartini; Susinggih Wijana; Widya D R Putri; Panji Deoranto (Journal of Innovation and Applied Technology, 2020)
One of the local commodities such as oranges is popular in Donowarih village. In harvesting season, a high waste material was produced due to rotten orange fruit.  Introducing post-harvesting technology to the community can help them to increase the economic values of the local commodities. The aim of this community development program was to transfer the technology and assist Donowarih Village to be one of the agro techno park (ATP) model in East Java. Several activities have been carried out include processing orange fruit into orange juice and orange jelly sweets. In this study, the creation of group-based agroindustry to process orange fruit has enable the group member to have more knowledge and skills, as well as potential additional income.